(untitled) (NAU Journal of Technology and Vocational Education, 2025)
This study examined the contributions and impediments of integrating Artificial Intelligence (AI) tools into project writing among business education students in colleges of education of Anambra State, Nigeria. The study was guided by two objectives and two corresponding research questions. The study adopted a descriptive survey design. The population consisted of 500 final-year business education students in selected colleges of education in Anambra State, Nigeria. Using stratified random sampling, 120 students were selected as the sample size. A structured questionnaire was used for data collection, and its reliability was established using Cronbach’s Alpha, yielding a coefficient of 0.81. Data were analyzed using descriptive statistics (mean and standard deviation). Findings revealed that students perceived AI tools as beneficial in enhancing the quality, speed, quality and structure of students’ project writing. However, impediments such as lack of technical know-how, over-dependence on AI, concerns about originality, and ethical implications were reported. The study recommends among others that institutions should incorporate AI literacy into the curriculum, train students on responsible AI use, and establish clear ethical guidelines for AI-assisted project writing for better academic performance. Further research should explore the long-term implications of AI integration on research culture and academic integrity.